2005
DOI: 10.1097/00007691-200502000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The pH Dependency of the Binding of Drugs to Plasma Proteins in Man

Abstract: An analysis of pH-induced changes of drug binding may contribute to the understanding of the mechanisms involved and the clinical relevance. A literature search was performed, and acceptance criteria set up, to select reported data for quantitative evaluation. The relationship between percentage of unbound drug, fu, and pH was analyzed, and the relevance of physicochemical characteristics of the ligand drugs and the importance of hydrogen ion-induced changes in plasma proteins for the pH sensitivity of the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 81 publications
4
37
0
Order By: Relevance
“…4, a-c, for which basic drugs in this pK a range show the most prominent shift in fup fold difference. For acids, the opposite would be expected; however, other groups have shown that some acids exhibit a decrease in fup with an increase in pH (Panjehshahin et al, 1992;Hinderling and Hartmann, 2005). We also observed this phenomenon for warfarin, which could potentially be due to a change in ionization of albumin, a charge-charge interaction with the lysine residue on albumin, or a change in conformation of albumin (Kasai-Morita et al, 1987).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…4, a-c, for which basic drugs in this pK a range show the most prominent shift in fup fold difference. For acids, the opposite would be expected; however, other groups have shown that some acids exhibit a decrease in fup with an increase in pH (Panjehshahin et al, 1992;Hinderling and Hartmann, 2005). We also observed this phenomenon for warfarin, which could potentially be due to a change in ionization of albumin, a charge-charge interaction with the lysine residue on albumin, or a change in conformation of albumin (Kasai-Morita et al, 1987).…”
Section: Discussionsupporting
confidence: 49%
“…It has been shown that an increase in plasma pH can have a significant influence on the extent of drug binding to plasma proteins (Paxton and Calder, 1983;Kremer et al, 1988;Hinderling and Hartmann, 2005;Wan and Rehngren, 2006;Kochansky et al, 2008). In attempts to address this issue, Wan and Rehngren (2006) determined that stronger buffers were required to minimize pH shifts, whereas others advocated the use of a 10% CO 2 atmosphere (Fura et al, 2003;Musteata et al, 2006;Kochansky et al, 2008) or initial purging of plasma with CO 2 followed by ultracentrifugation for determination of fup (Nilsson and Schmidt, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH changes in the postmortem environment apart from changes in ionisation states may also alter the plasma protein binding of drugs (such as morphine) due to changes in protein structure and protein denaturation. Increasing the amount of morphine available to freely diffuse in the postmortem environment [39] .…”
Section: Antemortem Morphine and Morphine-3-glucuronide Levelsmentioning
confidence: 99%
“…The fu of some drugs has been reported to rise with increasing temperature [20], but this is unlikely to be a significant issue in our study since previous reports used higher temperatures, and our fu values were slightly larger. Further, pH was not controlled, which is frequently the case with ultrafiltration [21]. This may be less relevant than for equilibrium dialysis because there is no exposure to an artificial buffer during ultrafiltration.…”
Section: Discussionmentioning
confidence: 99%